WISATA LUMBA-LUMBA DI PANTAI LOVINA DESA KALIBUKBUK, KABUPATEN BULELENG (STUDI KASUS ATRAKSI LUMBA-LUMBA DI HOTEL MELKA) - Anak Agung Ayu Ribeka Martha Purwahita; Anak Agung Sagung Srikandi; I Gusti Agung Budiasih; I Wayan Arka (Forum Manajemen, 2022)
Dolphin tourist attraction at Lovina Beach is one of the attractions to see dolphins on the high seas which is able to attract tourists to visit, as well as being a tourist attraction in North Bali. The development of dolphin tourism attractions has been shown in the swimming pool, but the survival of the dolphins is threatened. This case study discusses the exploitation of dolphins at the Melka Excelsior Hotel. This study aims to identify and analyze problems related to the exploitation of dolphins. Dolphin tourism attractions have positive and negative impacts and follow-up is needed to enjoy safe and comfortable dolphin tourism, especially dolphin conservation. The research method used is the field observation method and literature study obtained from journals and the internet. The placement of dolphins in the pond due to conditions that are not in accordance with their natural habitat will have a direct impact on these mammals. The activity of this dolphin attraction is more directed towards exploitation so that the need for dolphin conservation for commercial purposes does not have a positive effect on the dolphins themselves and lacks attention to these mammals.